Barriers to using clozapine in treatment-resistant schizophrenia: systematic review. (28th September 2018) - Farooq, Saeed; Choudry, Abid; Cohen, Dan; Naeem, Farooq; Ayub, Muhammad
Abstract : Aims and method: To systematically review the literature on barriers to the use of clozapine and identify any interventions for optimizing clozapine use in treatment-resistant schizophrenia. Journal databases were searched from 1972 to March 2018. The following search terms were used: treatment-resistant schizophrenia, clozapine, barriers, use, prescription rates, implementation, clozaril and prescribing practices. Following a review of the literature, 15 papers were included in the review. Results: The major barriers that were identified included mandatory blood testing, fear of serious side-effects and lack of adherence by the patients, difficulty in identifying suitable patients, service fragmentation, and inadequate training in or exposure to using clozapine. Clinical implications: In view of consistent evidence across the studies on inadequate knowledge and skills as a significant barrier, we suggest that a certification requiring competence in initiating and managing side-effects of clozapine becomes a mandatory requirement in training programmes. Declarations of interest: None.